Etica della Psichiatria - Maurizio, Gionni (Studia Bioethica, 2012)
Placing like premise the impossibility "not to change", it emerges, necessarily, in the context of the human-psychological development, the Ethical Problem of the Psychiatry and that note in relation to the direction of the unavoidable modification-change.